Answer:
y= -4
Step-by-step explanation:
x+y=42. We know that x plus y equals 42.
x=2y . We also know that x equals twice y.
2y+y=42. Since we know that x=2y, we're going to replace x with 2y from the original equation, simplified would be 3y=42.
y=14. 3y=42 simplified is y=14, this is because we divided both sides by 3 (since 3 and 42 are both divisible by 3) (btw divisible by 3 simply means that it can be divided by 3)
x+14=42. Now that we know what y equals, let's replace y with 14 from the original equation.
x=28. Now that we know that x=28 and y=14, we know that y is always x/2.
When x=-8, we divide it by 2 and get, -4.
Not absolutely positive as this was all mental math, but hope this helps! :)
Answer:
first of all erase what u have written
Step-by-step explanation:
<h2>Q: 25-(3x+5)=2(x+8)+x</h2>
- 25-3x-5=2x+16+x
- 20-6x=16
- 6x=4
- x=2/3
I don't understand what you're asking, is there supposed to be a picture with the question?
sin^2 x + 4 sinx +3 3 + sinx
-------------------------- = -------------------
cos^2 x 1 - sinx
factor the numerator
(sinx +3) (sinx+1) 3 + sinx
-------------------------- = -------------------
cos^2 x 1 - sinx
cos^2 = 1-sin^2x
(sinx +3) (sinx+1) 3 + sinx
-------------------------- = -------------------
1- sin^2x 1 - sinx
factor the denominator
(sinx +3) (sinx+1) 3 + sinx
-------------------------- = -------------------
(1-sinx ) (1+sinx) 1 - sinx
cancel the common term (1+sinx) and (sinx +1)
(sinx +3) 3 + sinx
-------------------------- = -------------------
(1-sinx ) 1 - sinx
reorder the first term
3+sinx 3 + sinx
-------------------------- = -------------------
(1-sinx ) 1 - sinx